Anomalous texture development induced by grain yielding anisotropy in Ni and Ni-Mo alloys. (November 2020) - Han, Lu; Jeurgens, Lars P.H.; Cancellieri, Claudia; Wang, Jing; Xu, Yifei; Huang, Yuan; Liu, Yongchang; Wang, Zumin
Abstract: During the annealing of Ni and Ni-Mo films, a {110} texture, usually considered to be both of high surface energy and high strain energy, was found to develop. Quantitative thermodynamic model calculations showed that the anomalous formation of this {110} texture originates fundamentally from the grain yielding anisotropy of Ni. Based on extensive grain yielding anisotropy model calculations, a "texture map" based on {111}, {100}, and {110} textures was constructed to predict the texture transition temperatures for different film thicknesses. A kinetic analysis of the texture evolution in the films is further presented, revealing that the texture evolution is controlled by the self-diffusion of atoms at grain boundaries. These findings pave the way for the achievement of unusual surface orientations through the quantitative texture design of thin films. Graphical abstract: Image, graphical abstract